Examining the Influence of Self-efficacy and Actively Caring on Safety Bahaviour - Abdullah, Nor Azimah Chew; Mat, Norazuwa; Raihan, Mohd Hasanur; Johari, Johanim (2014)
The aim of this study is to examine the relationship between self-efficacy, actively caring and safety behaviour. Data was gathered through questionnaires from a sample of medical laboratory technologists (n = 130) who worked in a research and diagnostic public medical hospital in Klang Valley, Malaysia. Using partial least squares (PLS) analysis method, the resub showed that self-efficacy and actively caring have positively influenced safety behaviour among respondents. Discussions articulated on the plausible explanations for the results. Finally, the theoretical and practical ramifications of this study are brought to fore.